(untitled) (Revista Ciência Agronômica, 2017)
The distribution of phosphorus (P) in the soil interferes with the availability of the nutrient and can affect plant growth. The aim of this study was to compare the growth and accumulation of P in maize, soybean and sunflower plants in vertical gradients of the nutrient in the soil, with and without water stress. The design was completely randomised with five replications, in a 3 x 2 factorial scheme: three soil depth gradients of P (decreasing, increasing and nil) and two conditions of soil water availability (with and with no water stress). The depth gradients of P were in decreasing doses of P2O5 (300, 200, 100 and 0 mg dm-3), increasing doses (0, 100, 200 and 300 mg dm-3) and equal doses (150 mg dm-3) applied to the intermediate layers between 0.0-5.0, 5.1-10.0, 10.1-15.0 and 15.1-20.0 cm. Height, dry weight and P accumulation in the roots and shoots were quantified. The data were submitted to analysis of variance, and mean values compared by Tukey’s test (p<0.05). The distribution of P in the soil did not interfere with growth or nutrient accumulation in the soybean. Phosphate fertiliser located in the surface or subsurface layers favoured greater growth and the accumulation of P in the maize and sunflower, compared to the uniform distribution of the nutrient in the 0-20 cm layer. The increase in phosphate fertiliser at depth did not increase growth or P accumulation in the three crops, even under conditions of water stress.